Meta-analysis of the association of AhR Arg554Lys, AhRR Pro185Ala, and ARNT Val189Val polymorphisms and endometriosis risk in Asians - Zheng, Neng-neng (J Assist Reprod Genet, 2015)
PURPOSE: Several studies have suggested an association between the polymorphisms AhR Arg554Lys, AhRR Pro185Ala, and ARNT Val189Val and endometriosis, but results have been inconclusive. The aim of the present study was to assess these associations by meta-analysis. METHODS: Eligible literatures were retrieved from PubMed, ISI Web of Science, Elsevier Science Direct, and several Chinese databases. The pooled odds ratios (ORs) and the corresponding 95 % confidence intervals (CIs) were calculated with a random or fixed-effect model. RESULTS: A total of six eligible studies were included. Regarding the AhR Arg554Lys and ARNT Val189Val polymorphisms, no obvious associations were found in either overall analysis or subgroup analysis based on the country, source of control, sample size, and genotyping method. For the AhRR Pro185Ala polymorphism, overall results suggested a marginal association with endometriosis susceptibility under the dominant model (OR = 1.65, 95 % CI = 1.00–2.72). Furthermore, a significantly increased risk for endometriosis was found in the subgroups which used the TaqMan method for genotype analysis or had a sample size ≥200. CONCLUSIONS: This meta-analysis suggested that the polymorphisms of AhR Arg554Lys and ARNT Val189Val are not associated with endometriosis, while the AhRR Pro185Ala polymorphism may be associated with endometriosis risk. However, further case–control studies with larger sample sizes are needed to confirm our results.